2017
DOI: 10.7863/ultra.16.05055
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater Reliability of Sonographic Optic Nerve Sheath Diameter Measurements by Emergency Medicine Physicians

Abstract: Although both resident and ultrasound fellowship-trained EM physicians showed good inter-rater reliability of ONSD measurements, variation in agreement among ultrasound fellowship-trained EM physicians may be as wide as 0.44, suggesting that even in skilled hands, ultrasound measurement of the ONSD may not be as dependable a screening tool for elevated intracranial pressure as previously suggested in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 10 publications
(20 reference statements)
1
29
0
1
Order By: Relevance
“…The degree of agreement for post hoc measurements of the ONSD was slightly lower, but still clinically acceptable, with an intrareader correlation coefficient at the lower end of the "optimal" range, and an interreader coefficient at the upper end of the "strong" range. This is not unexpected, given the technical challenges associated with this assessment, and is in keeping with the findings of earlier studies …”
Section: Discussionsupporting
confidence: 87%
“…The degree of agreement for post hoc measurements of the ONSD was slightly lower, but still clinically acceptable, with an intrareader correlation coefficient at the lower end of the "optimal" range, and an interreader coefficient at the upper end of the "strong" range. This is not unexpected, given the technical challenges associated with this assessment, and is in keeping with the findings of earlier studies …”
Section: Discussionsupporting
confidence: 87%
“…In the present study, although we didn't evaluate the ICC of emergency medicine residents, the ICC of ONST on facial CT was found to be over 0.9, which is remarkably high. 19 Additionally, we previously demonstrated that the ONSD on facial CT had a feasible predictive performance in identifying TBI. 15 Here, we found no difference between ONSD and ONST on facial CT.…”
Section: Discussionmentioning
confidence: 98%
“…Although standard portable ultrasound units have been extensively tested and have been determined to be reasonably accurate for measurement of ONSD and determination of ICP, [11][12][13]15,16 newer handheld units are continuously being added to the market. New pocket ultrasound devices are not identical to previously validated portable ultrasound, nor are they identical to the pocket Vscan unit that we have previously found to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…As with any ultrasound measurement, ONSD sonography has been shown to be operator dependent with small to moderate inter-observer and intra-observer variation reported in the literature. [11][12][13][14][15][16] It has been previously shown that this variance can be improved with practice. 15,17 There is growing evidence that simulation is effective for developing and assessing both technical and non-technical skills.…”
Section: Introductionmentioning
confidence: 99%